THE EFFECT OF BOUNDING ATTACHMENT EDUCATION ON INCREASING KNOWLEDGE OF PREGNANT WOMEN TRIMESTER III AT BPM H BENGKULU CITY - Juanda Syafita Sari (Placentum, 2025)
Normal baby development really depends on the loving response between mother and baby. This response can be formed through the bounding attachment process. The lack of loving response between mother and baby in the form of bounding attachment will affect the baby's development process such as stereotyped behavior, abnormal social behavior, motor, cognitive and verbal decline and can even increase the infant mortality rate (IMR). The aim of this research is to analyze the effect of bounding attachment education in increasing the knowledge of pregnant women in the third trimester at BPM H, Bengkulu city. The type of research used was Pre Experimental with a one group pre test-post test design, the population in this study were all pregnant women in BPM H, with a sample of 35 third trimester primigravida pregnant women using a purposive sampling technique. Using primary data, processed univariately and bivariately. This research was carried out from December 2023 to January 2024 at BPM H, Bengkulu city. The results of the univariate analysis, of the 35 pregnant women in the pre test, the majority, namely 26 (74.3%) respondents, had poor knowledge, in the post test the majority, namely 21 (60%) respondents, had good knowledge . The results of bivariate analysis using the one samples t-test showed ap value of 0.021, because ap value <0.05 means there was an increase in pregnant women's knowledge about bounding attachment after the intervention. It is hoped that health workers, especially midwives, will use health media to convey education to the public so that women, especially pregnant women, can increase their knowledge about bounding attachment.